Immersive Role-Playing: An Experience Report on a Promising Approach to Learning Requirements Elicitation - Otemaier, Kelly Rafaela; Albuquerque, Regina; Diniz, Rodolfo; Reinehr, Sheila; Malucelli, Andreia (Anais do Simpósio Brasileiro de Qualidade de Software (SBQS), 2024)
Developing the necessary skills in Software Engineering students to conduct interviews to elicit requirements is not a trivial activity. Immersive role-playing is a promising learning technique, allowing students to practice realistic interviews, receive real-time feedback, and improve their performance under pressure. This approach combines traditional role-playing with an immersive learning environment, offering an engaging and authentic experience that prepares students for the industry's challenges. This article aims to present an experience report on using immersive role-playing to teach the interview technique for eliciting software requirements. This experience was carried out with fifteen undergraduate students in Requirements Engineering. The results show the effectiveness of immersive role-playing in requirements elicitation, promoting increased engagement in tasks and authentic learning through feedback and reflection on mistakes made. The proposed immersive experience proved promising for improving education, engagement, and technical skills. Other skills relevant to training students in Software Engineering could also be worked on, such as oral communication, adaptability, and active listening.